Research Trends in Vascular Aging in the Last Decade: A Comprehensive Bibliometric Analysis - Shi D; Ning Z; Zhang Y; Guo X; Wei Y; Liu M (Vascular Health and Risk Management)
Dandan Shi,* Ziqi Ning,* Yaoyao Zhang, Xiaochen Guo, Yun Wei, Meixia Liu Xiyuan Hospital, China Academy of Chinese Medicine Science, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meixia Liu, Email liumeixia2004@126.com Yun Wei, Email weiyun_0913@163.comBackground: In recent years, vascular aging has emerged as a hot topic in become an important direction of aging research, but a comprehensive bibliometric analysis has not been conducted.Methods: The Web of Science database was searched for articles and reviews on vascular aging from January 1, 2014, to August 20, 2024, and the literature was analyzed and knowledge maps were constructed using CiteSpace, VOSviewer, pajek and Scimago Graphica software for econometric analysis and knowledge graph construction of the literature.Results: A total of 38,910 authors from 7622 institutions in 111 countries published 7277 papers in 1344 academic journals, with a significant increase in publication volume. The United States is the country with the highest productivity and citation rates, and Mayo Clinic is the most active institution. Tarantini S published the most papers, while Csiszar A received the most citations. Retina-The Journal of Retinal and Vitreous Diseases journal published the most papers, and Circulation journal received the most citations. The main research aspects include age-related macular degeneration, arteriosclerosis, and oxidative stress, which are the main keywords in this field. In the last decade, the term c reactive protein has attracted great attention with its strongest citation explosion.Conclusion: In the past decade, the research focus on vascular aging has been increasing year by year. Age-related macular degeneration, arteriosclerosis, oxidative stress and vascular endothelial cells are the emerging research directions in this field.Keywords: vascular aging, research trends, bibliometric analysis, visual analysis